Comparative analysis of Russian and international practice of liability insurance in medicine (Путеводитель предпринимателя)
The article presents the results of comparative research of physicians’ and medical organizations’ professional liability insurance in the U.S., UK, Canada and Russia. The article identifies institutional, organizational, legal, insurance features of foreign insurance practice that should be considered in the health insurance reform in Russia.